DAMPAK PENERAPAN AI TERHADAP PERAN PUSTAKAWAN DI ERA DIGITAL - Bifakhlina, Febriyanti (UIN Imam Bonjol Padang, 2024)
The development of artificial intelligence (AI) technology has reshaped various sectors, including libraries, which face new challenges and opportunities. This study aims to analyze the impact of AI implementation on the role of librarians in the digital era. Through literature review and case analysis, this research identifies significant changes in the tasks and responsibilities of librarians due to AI integration. The findings indicate that AI can automate routine tasks, such as cataloging, information retrieval, and collection management, allowing librarians to focus more on creative and strategic tasks, such as program development and user interaction. However, there are concerns about the potential replacement of librarians by AI. This study concludes that while the role of librarians will undergo significant transformation, they will remain relevant. Future librarians need to develop expertise in information technology, data analysis, and AI-based service development to provide greater added value to library users.